2003
DOI: 10.1046/j.1523-1755.2003.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hemodialysis-induced oxidative stress in end-stage renal disease patients by electrolyzed reduced water

Abstract: This study demonstrates that hemodialysis with ERW administration may efficiently increase the H2O2- and HOCl-dependent antioxidant defense and reduce H2O2- and HOCl-induced oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 35 publications
1
127
0
Order By: Relevance
“…Jin et al (9) and Kim et al (10) demonstrated anti-diabetic effect of ERW through the results of reduced blood glucose concentration, increased blood insulin level, improved glucose tolerance and preserved pancreatic β-cell mass using diabetic animal model. Huang et al (7,8) demonstrated the potential therapeutic effects of ERW through reduction of hemodialysis-induced oxidative stress and erythrocyte impairment in end-stage renal disease patients. ERW also has a tendency to suppress single-strand breakage of DNA induced by ROS in vitro (19) and selectively stimulates the growth of anaerobic microflora in the human intestinal tract (23).…”
Section: Referencesmentioning
confidence: 99%
“…Jin et al (9) and Kim et al (10) demonstrated anti-diabetic effect of ERW through the results of reduced blood glucose concentration, increased blood insulin level, improved glucose tolerance and preserved pancreatic β-cell mass using diabetic animal model. Huang et al (7,8) demonstrated the potential therapeutic effects of ERW through reduction of hemodialysis-induced oxidative stress and erythrocyte impairment in end-stage renal disease patients. ERW also has a tendency to suppress single-strand breakage of DNA induced by ROS in vitro (19) and selectively stimulates the growth of anaerobic microflora in the human intestinal tract (23).…”
Section: Referencesmentioning
confidence: 99%
“…However, this procedure can lead to oxidative stress causing cardiovascular disease. A clinical study was performed on 22 men and 15 women submitted to haemodialysis performed with ERAW provided by a commercial apparatus HD-24K (Nihon Trim Co., Osaka, Japan) that was adapted to a AF-150 haemodialyzer equipped with AF-150 membranes (Althane, Althin Medical Inc., Miami, FL, USA) [45]. The following blood parameters were measured: total anti-oxidant state (TAS), anti-oxidant activity of plasma, level of proteins/oxidised amino acids, lipid peroxidation, interleukin-6 (IL6) levels and the concentration of C-reactive protein.…”
Section: Haemodialysismentioning
confidence: 99%
“…Co, Sendai, Japan). 9 The recorded CL signals from the test mixtures containing plasma were referred to as plasma "reference H 2 O 2 counts" (pRH 2 O 2 ) or plasma "reference HOCl counts" (pRHOCl). A higher pRH 2 O 2 or pRHOCl indicated higher ROS activity or lower antioxidative activity (lower ROS scavenging ability), or both, in plasma.…”
Section: Measurement Of Specific Plasma Antioxidant Activitymentioning
confidence: 99%
“…5 The increased oxidative stress can cause oxidation of biological macromolecules, including proteins and lipids. 6,7 The 2 major ROS generated from activated PMNs via the myeloperoxidase (MPO) system are hydrogen peroxide (H 2 O 2 ) and hypochlorite (HOCl), 8 which can produce lipid peroxidation products, malonealdehyde (MDA), and phosphatidylcholine hydroperoxide (PCOOH) 9,10 and protein oxidation products, diotyrosine and methylguanidine, as indirect indicators of ROS and/or free radical activity. 11,12 Among these oxidized products, oxidized LDL (oxLDL) can increase the adhesion of monocytes to the endothelium and transformation of macrophages into foam cells and impair endothe-lium-dependent vasorelaxation.…”
mentioning
confidence: 99%